Analisis Kualitas Pelayanan Publik di Kantor Kelurahan Kotabaru Kecamatan Cibeureum Kota Tasikmalaya - Iskandar, Ade; Kornelia, Kornelia; Lakoni, Lakoni (Universitas Bandar Lampung (UBL), 2024)
This study aims to assess the quality of public services at the Kotabaru Village Office and identify factors that support and hinder these services. The research was conducted in Kotabaru Village, Cibeureum Subdistrict, Tasikmalaya City using observation and interview methods with service providers and users, with data analysis using qualitative descriptive analysis. Data collection included observation, interviews, and documentation, with interviews conducted with seven respondents. The research findings show that public services at the Cibeureum District Office have generally been running well. The main factors affecting service quality include employee discipline, availability of equipment and facilities, availability of service standards, and guarantee of cost and timeliness in the service process. Supporting aspects of service quality are employee discipline, showing good performance and behaviour, employee responsiveness to service users, guaranteeing timely service processes. The inhibiting aspects of service quality are lack of equipment and facilities, absence of clear service standards, uncertainty in the service process.